Happiness, pride and elite sporting success: What population segments gain most from national athletic achievements? - Hallmann, K.; Breuer, C.; Kühnreich, B. (Sport Management Review, 2013)
Elite sports are widely considered by national governments as a merit good through which many benefits to society as whole can be fostered through the stimulation of `national pride` and `happiness` (or `wellbeing`). The aim of this paper is to analyze what factors influence perceived national pride and happiness when athletes succeed at major national and/or international competitions. Based on a nation-wide survey, data was collected from n = 2006 randomly selected Germans by means of a computer assisted telephone interview. The results reveal that 66.2% respondents felt proud and 65.6% respondents were happy when German athletes were successful at major events. National pride and happiness were significantly explained through interest in elite sports, sport participation and socio-economic variables. The results reveal that there are differences between the perception of pride and that of happiness. Women, individuals with a low educational background, and low income and individuals having a migration background are the population segments who gain most from the sporting success of elite athletes. The results show in particular that the funding of elite sports and elite athletes can be considered as policy tool for social integration